Risk and Organizational Ambidexterity: A Meta-Synthesis of a Case Study and a Framework - Elizandra Severgnini; Adriana Roseli Wünsch Takahashi; Gustavo Abib (BBR: Brazilian Business Review)
Organizational ambidexterity arises as an organization’s ability to employ efforts on contradictory goals, such as exploration and exploitation for long-term success and long-lasting performance. In addition, the organization faces risks inherent in the management of its administrative capacity. However, to date, we did not find a systematic qualitative-research review on risk and organizational ambidexterity. This paper fills this gap by systematically reviewing existing qualitative case studies on risk and organizational ambidexterity published in peer-reviewed journals. To fulfill this objective, we used a meta-synthesis of qualitative synthesis case studies in order to identify possible cause and effect relationships between the constructs and to propose a theoretical model. The results showed that risk and uncertainty influence the way the organization invests resources in exploration or in exploitation. Second, the findings indicated that risk moderates the direct effect of exploration and exploitation on performance and on decision making, amplifying or reducing their effects. Third, the framework suggests that risk has a direct effect on organizational performance, reducing it, or influencing strategic decision-making (ranging from intuitive to rational decision).